2020
DOI: 10.1371/journal.pone.0239419
|View full text |Cite
|
Sign up to set email alerts
|

Further investigation of the effects of wearing the hijab: Perception of female facial attractiveness by Emirati Muslim men living in their native Muslim country

Abstract: The hijab is central to the lives of Muslim women across the world but little is known about the actual effects exerted by this garment on perceptions of the wearer. Indeed, while previous research has suggested that wearing the hijab may affect the physical attractiveness of women, the actual effect of wearing the hijab on perceptions of female facial attractiveness by Muslim men in a Muslim country is largely unknown. Accordingly, this study investigated the effects of the hijab on female facial attractivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 56 publications
4
12
1
Order By: Relevance
“…22 Faces where heads were uncovered or partially covered were rated as equally attractive, and both were rated more substantially to be more attractive by men than faces where heads were fully covered. 23,24 Pazhoohi and Hosseinchari 25 showed that men were more motivated to view women exhibiting the less veiling and rated them more attractive than those women whose bodily curves were less visible. These results show that the hijab suppressed female attractiveness to both men and women.…”
Section: The Hijab From Past To Presentmentioning
confidence: 99%
“…22 Faces where heads were uncovered or partially covered were rated as equally attractive, and both were rated more substantially to be more attractive by men than faces where heads were fully covered. 23,24 Pazhoohi and Hosseinchari 25 showed that men were more motivated to view women exhibiting the less veiling and rated them more attractive than those women whose bodily curves were less visible. These results show that the hijab suppressed female attractiveness to both men and women.…”
Section: The Hijab From Past To Presentmentioning
confidence: 99%
“…The attractiveness of female face was lower as compared to fully covered. Partial and uncovered appeared more attractive to men as a general perspective [24]. This study is quite different and do not match with the present study but interesting perceptions were noted.…”
Section: Discussioncontrasting
confidence: 99%
“…There are at least three candidate reasons for this. A first possible source of different responses among men and women is the fact that men, including Muslim men in Islamic States where the hijab is commonplace, consistently judge women who wear the hijab less facially attractive than women who appear with uncovered hair [29,30]. If attractiveness has an impact on overall person evaluation, and assuming that women's judgments of attractiveness are unaffected by the hijab, men's appraisals of hijab-wearing women should be more negative than those of women, leading to a more important decrease in nonverbal involvement and similarly in the probability of offering assistance ("attractiveness hypothesis").…”
Section: Conceptual Frameworkmentioning
confidence: 99%